Long-term organic and inorganic fertilization on economics, energy budgeting and carbon footprint of soybean-wheat cropping system in the Indian mid-Himalayas. Issue 14 (6th December 2022) - Parihar, Manoj; Panday, Suresh Chandra; Meena, Rajendra Prasad; Kumar, Utkarsh; Meena, Vijay Singh; Choudhary, Mahipal; Singh, Ashish Kumar; Bisht, Jaideep Kumar; Kant, Lakshmi; Pattanayak, Arunava
ABSTRACT: For identification and adoption of improved and environmental friendly agricultural practices with minimum emission of greenhouse gases (GHGs), observations were recorded for 3 years (2015–17) in a 22-year-old soybean-wheat based long-term fertilizer experiment that was started in 1995–96. The study involved seven treatments: control (CK), organic manure (M), inorganic fertilizers (NPK), integrated (MNPK), only nitrogen (N), mineral fertilizers in both season (NPK+NPK) and nitrogen with organic manure (MN). MNPK significantly enhanced the system productivity (9.72 Mg ha −1 ) with higher net return (3128 USha −1 ) and benefit-cost ratio (1.64). Due to better energy output to inputs relation, total energy productivity and energy use efficiency were reported higher in MNPK (0.38 kg MJ −1 and 4.76, respectively) followed by MN (0.34 kg MJ −1 and 4.26, respectively) and M (0.32 kg MJ −1 and 4.16, respectively). In contrast to C efficiency, C sustainability index and yield scaled carbon footprint (CFy), the spatial CO2 -e emission (CFs) was found highest under MNPK ( 5035 kg CO2 -e ha −1 ) followed by MN and NPK+NPK and lowest was recorded under control. In sum, long-term organic and inorganic fertilization simultaneously in soybean-wheat system may be a preferred strategy for improving soil productivity, profitability, energy use and environmental sustainability of Indian-mid-Himalayas.